Beyond Criminality: Unveiling the Untold Kathoey Narratives in Thai-Language News Headlines. - Sreejak, Thanawut (Sexuality & Culture, 2026)
This study examines the portrayal of kathoeys (transgender women and feminine gay men) in Thai-language news headlines (N = 1,265) through Corpus-Assisted Discourse Studies and Queer and Trans Linguistics frameworks. Findings reveal persistent patterns of representation that construct kathoeys through binary extremes, either as perpetrators of sensationalized crimes or as exceptional figures in entertainment and beauty. While emerging counter-narratives present kathoeys in advocacy roles, these remain marginal and conditional, reinforcing rather than challenging normative expectations. The findings demonstrate how linguistic choices in headlines, particularly collocations with terms indicating deviance or spectacle, contribute to kathoeys' continued marginalization in Thai media discourse. This systematic othering persists despite growing visibility, suggesting the need for fundamental changes in journalistic practices to promote a more nuanced and dignified representation of gender diversity in Thailand.